Utility of the Repeat and Point Test for Subtyping Patients With Primary Progressive Aphasia. (7th January 2022) - Seckin, Mustafa; Ricard, Ingrid; Raiser, Theresa; Heitkamp, Nari; Ebert, Anne; Prix, Catharina; Levin, Johannes; Diehl-Schmid, Janine; Riedl, Lina; Roßmeier, Carola; Hoen, Nora; Schroeter, Matthias L.; et al.
Abstract : Background: Primary progressive aphasia (PPA) may present with three distinct clinical sybtypes: semantic variant PPA (svPPA), nonfluent/agrammatic variant PPA (nfvPPA), and logopenic variant PPA (lvPPA). Objective: The aim was to examine the utility of the German version of the Repeat and Point (R&P) Test for subtyping patients with PPA. Method: During the R&P Test, the examiner reads out aloud a noun and the participants are asked to repeat the word and subsequently point to the corresponding picture. Data from 204 patients (68 svPPA, 85 nfvPPA, and 51 lvPPA) and 33 healthy controls were analyzed. Results: Controls completed both tasks with >90% accuracy. Patients with svPPA had high scores in repetition (mean=9.2±1.32) but low scores in pointing (mean=6±2.52). In contrast, patients with nfvPPA and lvPPA performed comparably in both tasks with lower scores in repetition (mean=7.4±2.7 for nfvPPA and 8.2±2.34 for lvPPA) but higher scores in pointing (mean=8.9±1.41 for nfvPPA and 8.6±1.62 for lvPPA). The R&P Test had high accuracy discriminating svPPA from nfvPPA (83% accuracy) and lvPPA (79% accuracy). However, there was low accuracy discriminating nfvPPA from lvPPA (<60%). Conclusion: The R&P Test helps to differentiate svPPA from 2 nonsemantic variants (nfvPPA and lvPPA). However, additional tests are required for the differentiation of nfvPPA and lvPPA.